(untitled) (CAHIERS MAGELLANES-NS, 2024)
Throughout their lives, women encounter violence on different scales, in different contexts, and to varying degrees. Women from the underprivileged groups in society are far more aware of this. Women employed in agriculture and plantation industries suffer the fury of oppressive working conditions. Various investigations have shown significant incidences of violence against women in Assam's tea gardens. The poor working conditions prevalent in tea gardens have long been a source of concern for the working women there. India's tea industry, particularly in Assam, makes a significant contribution to the GDP of the nation. Due to their ability to do the most crucial operation in the manufacturing process—plucking tea leaves—women workers in the tea gardens are considered as crucial agents in this process. However, women's status in society is not positively correlated with this really important labour that they undertake. The vulnerability of women in the tea gardens poses a threat to their advancement. Despite being referred to be a „feminised industry‟ by some scholars, the tea industry has not done enough to fairly treat the large number of women who work in it. The goals of government programmes are also to increase voter turnout in the tea gardens and provide little to no relief to the women workers. Thus, considering an array of patriarchal notions that are at play in the tea garden settings, this research paper attempts to examine gender-based violence against women in Assam‟s tea gardens specifically through an empirical lens.